Editor's foreword - Daly, Ann (Henry Stewart Talks, 2007)
Genes and gene products, Role of CYP2A6, CYP2B6, CYP2C8, CYP2C9, CYP2C19, CYP2D6 and CYP2E1 in drug metabolism, Regulation of gene expression, Effect of genetic variation, Clinically relevant polymorphisms
Reviewed at 2016/03/01